Pleiotropic vasoprotective effects of high-dose atorvastatin therapy in the context of achieving the target low-density lipoprotein cholesterol in patients after myocardial infarction - L. I. Salyamova; A. A. Khromova; O. G. Kvasova; K. N. Korenkova; K. N. Polezhaeva; N. A. Donetskaya; K. I. Pavlenko (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the lipid-lowering and pleiotropic vasoprotective effects of atorvastatin depending on the achievement of the target low-density lipoprotein cholesterol (LDL-C) level in patients after ST-segment elevation myocardial infarction (STEMI) within 48-week follow-up period.Material and methods. A total of 125 patients with STEMI, randomized to receive atorvastatin 40 or 80 mg per day for 48 weeks, were examined. On days 7-9, after 24, 48 weeks, we performed biochemical blood tests, echocardiography, as well as assessed the carotid arteries and endothelial function. The subjects were divided into the following groups: high-efficiency therapy (HET) — 41 patients who reached target LDL-C at control visits; moderate-efficiency therapy (MET) — 35 patients who achieved target LDL-C at one visit; low-efficiency therapy effective (LET) — 49 people who did not reach the target LDL-C. Differences were considered significant at p<0,05.Results. A decrease in detection rate of an elevated brain natriuretic peptide was found in HET group from 41,5 to 17% (p<0,01) and in MET group from 48,6 to 23% (p<0,01), while no changes in the LET were revealed. The glomerular filtration rate in the LET group decreased by 8% (p<0,01). In the HET group, a decrease in arterial elastance by 9,4%, intima-media thickness by 9,9%, a decrease in the frequency of a negative response and an increase in a positive response (p<0,05) were revealed.Conclusion. The results demonstrate the importance of achieving target LDL-C for the most favorable dynamics of brain natriuretic peptide, structural and functional characteristics of the arterial system.